2015
DOI: 10.4172/2329-9088.1000184
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Risk indices in Type 2 Diabetes Mellitus

Abstract: Background: Dyslipidemia a common feature of diabetes mellitus leads to cardiovascular complications. These complications are not detected early enough due to absence of cheap and routine biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…According to American Heart Association, a value of (>3.5) shows greater propensity towards cardiovascular diseases. Adu et al [10] also reported a significant increase value of Atherogenic Coefficient (Ac) of diabetes when compared with the non-diabetes subjects which is in agreement with the work of Ikewuchi [11].…”
Section: Introductionsupporting
confidence: 83%
“…According to American Heart Association, a value of (>3.5) shows greater propensity towards cardiovascular diseases. Adu et al [10] also reported a significant increase value of Atherogenic Coefficient (Ac) of diabetes when compared with the non-diabetes subjects which is in agreement with the work of Ikewuchi [11].…”
Section: Introductionsupporting
confidence: 83%
“…Atherogenic coefficient (Ac) was computed as TC-HDL/HDL, while cardiac risk ratio (CRR) was determined as TC/HDL. [2] Data management and analysis plan…”
Section: Sample Sizementioning
confidence: 99%
“…[1] This range of altered parameters in adults has been linked to deaths around the world on various continents with micro and macrovascular complications. [2] Since LDL cholesterol measurement alone is insufficient for risk identification, low-density lipoprotein (LDL) cholesterol concentration has been the primary source of cardiovascular disease risk and the main focus of intervention. [1,2] Although some studies continue to link LDL-C to CVD, the connection was modest, and LDL-C was not a reliable indicator of Death from coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations